Broncho-Pleural Fistula with Hydropneumothorax at CT: Diagnostic Implications in Mycobacterium avium Complex Lung Disease with Pleural Involvement - Yoon, Hyun Jung (Korean J Radiol, 2016)
OBJECTIVE: To determine the patho-mechanism of pleural effusion or hydropneumothorax in Mycobacterium avium complex (MAC) lung disease through the computed tomographic (CT) findings. MATERIALS AND METHODS: We retrospectively collected data from 5 patients who had pleural fluid samples that were culture-positive for MAC between January 2001 and December 2013. The clinical findings were investigated and the radiological findings on chest CT were reviewed by 2 radiologists. RESULTS: The 5 patients were all male with a median age of 77 and all had underlying comorbid conditions. Pleural fluid analysis revealed a wide range of white blood cell counts (410–100690/µL). The causative microorganisms were determined as Mycobacterium avium and Mycobacterium intracellulare in 1 and 4 patients, respectively. Radiologically, the peripheral portion of the involved lung demonstrated fibro-bullous changes or cavitary lesions causing lung destruction, reflecting the chronic, insidious nature of MAC lung disease. All patients had broncho-pleural fistulas (BPFs) and pneumothorax was accompanied with pleural effusion. CONCLUSION: In patients with underlying MAC lung disease who present with pleural effusion, the presence of BPFs and pleural air on CT imaging are indicative that spread of MAC infection is the cause of the effusion.